Genetic determinants and epigenetic effects of pioneer-factor occupancy. (February 2018) - Donaghey, Julie; Thakurela, Sudhir; Charlton, Jocelyn; Chen, Jennifer S.; Smith, Zachary; Gu, Hongcang; Pop, Ramona; Clement, Kendell; Stamenova, Elena K.; Karnik, Rahul; Kelley, David; Gifford, Casey; et al.
Abstract Transcription factors (TFs) direct developmental transitions by binding to target DNA sequences, influencing gene expression and establishing complex gene-regultory networks. To systematically determine the molecular components that enable or constrain TF activity, we investigated the genomic occupancy of FOXA2, GATA4 and OCT4 in several cell types. Despite their classification as pioneer factors, all three TFs exhibit cell-type-specific binding, even when supraphysiologically and ectopically expressed. However, FOXA2 and GATA4 can be distinguished by low enrichment at loci that are highly occupied by these factors in alternative cell types. We find that expression of additional cofactors increases enrichment at a subset of these sites. Finally, FOXA2 occupancy and changes to DNA accessibility can occur in G1 -arrested cells, but subsequent loss of DNA methylation requires DNA replication. Investigation of FOXA2, GATA4 and OCT4 binding across several cell types provides insights into the genetic determinants and epigenetic effects of pioneer-factor occupancy. The data suggest that FOXA2 samples most of its potential binding sites but is stabilized at only a subset of targets.